CNSC-19. GLIOMA-INDUCED NEURONAL REMODELING PROMOTES REGIONAL IMMUNOSUPPRESSION. (14th November 2022) - Nejo, Takahide; Krishna, Saritha; Young, Jacob S; Yamamichi, Akane; Jimenez, Christian; Chen, Tiffany; Watchmaker, Payal; Choudhury, Abrar; Diebold, David; Ogino, Hirokazu; Raleigh, David; Hervey-Jumper, Shawn L; et al.
Abstract: Gliomas remodel neuronal circuits and distinct intratumoral regions maintain functional connectivity through a subpopulation of synaptogenic malignant cells expressing Thrombospondin-1 (TSP-1, encoded by the Thbs1 gene). Single-cell RNA sequencing analyses of primary patient samples identified a significant downregulation of immune response in myeloid cells and lymphoid cells in high functionally connected intratumoral regions characterized by upregulated TSP-1. Understanding the functional significance of immunosuppression within functionally connected intratumoral regions may uncover therapeutic vulnerabilities. Here, we investigate glioma-neuronal-immune crosstalk across clinical tumor specimens and preclinical syngeneic models through bulk and single-cell RNA sequencing (13, 670 cells), flow cytometry, and spatial transcriptomics. Using an SB28 murine glioma cell line with endogenous Thbs1 stably expressed, we generated a CRISPR Thbs1 -knock-out (KO) cell line. Bulk RNA-sequencing demonstrated that Thbs1 -WT tumors exhibited gene expression programming consistent with synapse-associated genes and synaptogenic factors, recapitulating enriched connectivity in primary patient samples. Flow cytometry of brain-infiltrating leukocytes revealed that macrophages isolated from Thbs1 -KO tumors were more frequently polarized into the pro-inflammatory "M1-like" phenotype (median M1/M2 ratio = 0.6 [WT] vs 1.34 [KO], p < 0.006). Unbiased gene expression program analysis using spatial transcriptomics for in vivo tumor-harboring mouse brains demonstrated a significant spatial overlap of signatures of synaptogenesis (represented by Ntng1 and Nlgn3 genes) and downregulated immune response (represented by Nfkb1 and Cd83 genes). SB28- Thbs1 -KO syngeneic models demonstrated slower tumor growth and significantly longer survival compared to Thbs1 -WT counterparts (19 days [WT] vs 25 days [KO], p < 4.5E-5). The survival difference was abrogated in the B6-SCID immunodeficient mice, indicating the critical role of adaptive immunity in the survival advantage associated with TSP-1 inhibition. Our results identify previously unknown immunosuppression mechanisms in the context of glioma-induced intratumoral connectivity via Thbs1 . Future therapeutic strategies targeting this glioma-neuronal-immune crosstalk may open up new avenues for glioblastoma immunotherapy.